2007
DOI: 10.1039/b700957g
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesis of 2,3-dihydroquinazolin-4(1H)-ones in ionic liquids or ionic liquid–water without additional catalyst

Abstract: 2,3-Dihydroquinazolin-4(1H)-ones have been synthesized in high to excellent yields through direct cyclocondensation of anthranilamides and aldehydes in ionic liquids (ILs) or one-pot three-component cyclocondensation of isatoic anhydrides, ammonium acetate and aldehydes in ionic liquid-water solvent system without the use of any additional catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(79 citation statements)
references
References 30 publications
0
78
0
1
Order By: Relevance
“…It is probably due to a less organized structure of pyridinium ILs in comparison to imidazolium ILs. [16,17] Michael addition of 2 to 1 in [empyr]SO 4 Et with 5 mol-% of pyridine as catalyst proceeded with a rate constant of 0.26 ϫ 10 -4 s -1 (Table 1, Entry 21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is probably due to a less organized structure of pyridinium ILs in comparison to imidazolium ILs. [16,17] Michael addition of 2 to 1 in [empyr]SO 4 Et with 5 mol-% of pyridine as catalyst proceeded with a rate constant of 0.26 ϫ 10 -4 s -1 (Table 1, Entry 21).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we wondered what would be the reaction rate for the addition of 2 to 1 in some binary mixtures of imidazolium-based ILs. The results are collected in 4 Et anion can, in the presence of traces amount of water, hydrolyze to the HSO 4 anion, which can protonate the residual N-methylimidazole. Our observations are in accordance with the results of D'Anna [22] that the effect of binary mixtures [bmim]X/cosolvent on the reaction course cannot be ascribable to simple polarity, viscosity, or conductivity effects, but a whole set of parameters has to be considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several reports on the synthesis 2,3-disubstuted-2,3-dihydroquinazoline-4(1H)-one derivatives, [14,15] yet the investigations for a convenient and green synthesis is on due to different drawbacks in the existing methods, e.g., harsh reaction conditions, using toxic solvents and metal-based catalysts, low yield, time consuming, and no easy available precursors. Chen et al [16] has reported a new method for the preparation of 2,3-dihydroquinazoline-4(1H)-ones using classic ionic liquids such as [ À anions toward hydrolysis in contact with moisture, forming HF and POF 3 , which can dissolve glassware and damage steel autoclaves and reactors [17].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to their promising biological potential and wide occurrence in nature, several efforts have been made to develop an elegant approach for their synthesis. These include condensation of anthranilamide with aldehydes in presence of acid catalysts 4,5 reductive cyclization of Onitrobenzamide or O-azido-benzamide with aldehydes and ketones using SmI 2 , 6 or using TiCl 4 , 7, 8 reductive desulfurization of 2-thioxo-3H-quinazolin-4-ones with nickel boride in dry methanol, 9 one-pot conversion from 2-nitro-N-arylbenzamides using SnCl 2 , 10 one-pot synthesis using pTSA, 11 silica-SO 3 H, 12 alum, 13 montmorillonite K-10, 14 ionic liquids, 15 and gallium(III) triflate, 16 and enantioselective synthesis using chiral auxillary 3 and Bronsted acid catalyst. 17 Of these, the condensation of anthranilamide with aldehyde or ketone is one of the simplest and …”
Section: Introductionmentioning
confidence: 99%